Muscular ventricular septal defect closure with Gianturco coil at Soetomo hospital (a case report) - Alit Utamayasa; Teddy Ontoseno; Mahrus A Rahman; Vinny Yoanna; Rio Herdyanto (Indonesian Pediatric Society, 2010)
Ventricular septal defect (VSD) is the mostcommon congenital heart disease (CHD)in children.1'2 It occurs in 1.5 to 3.5 of1,000 live births and constitutes 20% ofcongenital cardiac defects.1 The VSD may be small,medium or large and is classified based on its locationin the interventricular septum. There are four types ofVSD, i.e., perimembranous (80% ofVSDs), musculartype (5% to 20%) inlet or AV canal type (8%), andfinally, subpulmonary (5% to 7%).1-4 When multiplemuscular defects are seen, it is often referred to as